2011
DOI: 10.1080/09537287.2010.491490
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study of ERP implementation in Saudi Arabia

Abstract: Enterprise resource planning (ERP) is being implemented by many organisations as a potential solution to their businesses. In spite of its appeal, ERP has challenges and difficulties in its realisation, especially in developing countries. In this article, existing trends and success factors for ERP implementation in Saudi Arabia is investigated. The results of this study apply, to a large extent, to other developing countries in the Middle East and other oil producing countries. The study captures the best imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 14 publications
0
25
0
Order By: Relevance
“…Some studies defined failure and success using grading scales: complete success, partial success, and complete failure [20].  Although the failure issue occurs primarily in industry as opposed to academia, almost all the reviewed studies were conducted by academics, which is indicative of a gap between industry and academia in SA.…”
Section: Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies defined failure and success using grading scales: complete success, partial success, and complete failure [20].  Although the failure issue occurs primarily in industry as opposed to academia, almost all the reviewed studies were conducted by academics, which is indicative of a gap between industry and academia in SA.…”
Section: Observationsmentioning
confidence: 99%
“…In general, management/leadership skills and organization culture were cited by [13][17], [20], [24], [26], [29], [32] as an important success criterion in IT projects.…”
Section: Observationsmentioning
confidence: 99%
“…As such, understanding context factors for ERP implementation is imperative because these factors might be unique to organizational culture or business processes that would significantly influence how ERP projects are carried out (Dezdar and Ainin, 2011;Kouki, Poulin and Pellerin, 2010). Recent empirical literature has thus witnessed increasing attention paid to unique local contexts such as China (Chien et al, 2007;Martinsons, 2004;Reimers, 2003), India (Poti and Kamalanabhan, 2009;Tarafdar and Roy, 2003) and the Middle East (Al-Turki, 2011;Amid, Moalagh and Zare Ravasan, 2012;Baki and Çakar, 2005). However, no empirical study has been found in the UAE context or based on contrasting theoretical frameworks.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, ERP systems as advanced technologies have been implemented in many HEIs in the KSA to improve their performance and efficiency. As a consequence, several studies have been conducted on the ERP implementation in the KSA (e.g., AL-Hudhaif, 2012;Al-Muharfi, 2014;Al-Turki, 2011;Saleh, Abbad, & Al-Shehri, 2013) with the emphasis on the general technical aspects and the CFSs. Thus, the post-implementation impacts of ERP were not widely investigated in these studies.…”
Section: Erp Systems In Heismentioning
confidence: 99%